2012
DOI: 10.3945/jn.111.146464
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Breads Containing In Situ–Produced Arabinoxylan Oligosaccharides Alters Gastrointestinal Effects in Healthy Volunteers3

Abstract: Arabinoxylan oligosaccharides (AXOS) are studied as food compounds with prebiotic potential. Here, the impact of consumption of breads with in situ-produced AXOS on intestinal fermentation and overall gastrointestinal characteristics was evaluated in a completely randomized, double-blind, controlled, cross-over study. Twenty-seven healthy volunteers consumed 180 g of wheat/rye bread with or without in situ-produced AXOS (WR(+) and WR(-), respectively) daily for 3 wk. Consumption of WR(+) corresponded to an AXO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 37 publications
2
58
1
1
Order By: Relevance
“…gasseri combined with L . coryniformis [38], FOS [39] and arabinoxylan oligosaccharides [40] significantly increased stool frequency in healthy adults. In contrast, L .…”
Section: Discussionmentioning
confidence: 99%
“…gasseri combined with L . coryniformis [38], FOS [39] and arabinoxylan oligosaccharides [40] significantly increased stool frequency in healthy adults. In contrast, L .…”
Section: Discussionmentioning
confidence: 99%
“…The total AX content of bread was calculated as described by Damen et al, 2012, [31] using concentrations of arabinose, galactose, xylose. As the anhydroxylose and anhydroarabinose units in AX are hydrated upon hydrolysis, a correction for this molecular mass shift has been incorporated in the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…However, a study with 14 participants consuming 15 g/day showed that while post-prandial glucose and insulin were lower, there was no change over five weeks in blood lipids, body weight, fat mass, or blood pressure [56]. Additionally, arabinoxylan-oligosaccharide, a fiber produced by enzymatic manipulation of arabinoxylan that has been studied as a prebiotic [57,58], also did not have an effect on blood lipids after three weeks [57]. …”
Section: Arabinoxylanmentioning
confidence: 99%